Problems Faced by the Teacher in Maximizing the Use of Learning Media in Padang - Tamrin, M; Azkiya, Hidayati; Sari, Syafni Gustina (AT-TALIM, 2017)
This research aims to find the teacher condition in teaching relating to the use of instructional media. This study used   descriptive qualitative method to gain the data in which the the researcher play his role as the major Instrument and put the teachers as the key informant while the secondary informant is the principal. The results of the research shows that the teachers were satisfied with what he/she has always do, and they feel there is no need to be changed or developed on the pattern of teaching and learning with the help of the media. This research conclude that teachers  assumee that teaching does not suported by various types of media and it make them have lack ability to use the learning media.  Finally, this reseach recomend the teacher to change their habbit in using the media while the school leader provide them with opportunities to utilize the media in their teaching process.